Natural variation of wheat cuticular waxes in relation to drought tolerance - Bi, H.; Kovalchuk, N.V.; Dias, D.; Roessner, U.; Langridge, P.; Lopato, S.; Borisjuk, N.V. (Фактори експериментальної еволюції організмів, 2015)
Aims. The aim of our research is to investigate the role of wheat leaf cuticle in drought and heat protection by characterizing
natural variability of cuticle components and revealing genetic and biochemical background of this variability in Australian
wheat varieties. Methods. Cultivars with different levels of drought tolerance were analyzed for cuticle wax composition
by gas chromatography (GC–MS) and for cuticle structure properties by scanning electron microscopy (SEM). Results.
Metabolomics analyses demonstrated signifi cant quantitative differences between drought-sensitive and drought-tolerant
cultivars in several types of wax components. These data are complemented by differences in cuticle structure revealed
by SEM. Ten wheat genes potentially involved in regulation of cuticle biosynthesis have been cloned and analysed for
expression profi les in wheat by RT-qPCT. Conclusions. Acquired data are currently being used for identifi cation of
enzymes and genes responsible for drought-related cuticular components.
Keywords: wheat, drought tolerance, cuticle waxes, gene expression.